Implementación del estudio de casos como estrategia de prevención de la responsabilidad penal en los estudiantes de las instituciones educativas oficiales del municipio de Soledad (2019)
The problems in the Municipality of Soledad by minors and adolescents in their behaviors of rebellion, irresponsibility, aggressiveness, which often culminate in inappropriate or criminal behavior, are consequences of measures of assurance with or deprivation of liberty; situations that are reflected and evidenced in the Official Educational Institutions affecting the School coexistence and exposing the other students at risk; it is for this reason that the Rectors and the administrative authorities are jointly with the educational community to implement strategies for the social and school impact that this problem generates and that with the passage of the years has been increasing by leaps and bounds, by itself, with the implementation of this Project through the teaching of Criminal Responsibility to the student to be aware of their actions, to know their consequences, to strengthen the values and to acquire the ability to discern in the resolution conflicts in a favorable and that because they are minors and adolescents the best way to do through the didactics as a stimulating pedagogic strategy, great impact, innovative that strengthens the citizen competences of Coexistence and Peace, Participation and democratic Responsibility Plurality, identity and valuation of differences; in order to strengthen the learning of the healthy coexistence and good school behavior of the students of the Official Educational Institutions of the Municipality of Soledad.